Handbook of cyber laws - Sharma, Vakul (New Delhi, 2002)
The aim of this book is to provide comprehensive knowledge to the reader navigating the roads of cyberworld. From e-commerce to e-signatures to e-acts, this book has everything. It talks in terms of 'everyday applications' of the Internet in jargon-free and simple language. Many illustrations are provided to make things easy and interesting.
Keywords: Cyber laws